PENGARUH LATIHAN TRIANGLE RUN TERHADAP DAYA TAHAN AEROBIK PADA TIM BOLA VOLI PUTRA GENERATION CLUB PEKANBARU - M Sholeh Handika; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted to find out whether there was an effect of Triangle run exercise in aerobic endurance on volleyball team man of Generation Club Pekanbaru, with the result that during the competition athletes always experience excessive fatigue. This research was experimental research, the population was volleyball players in Generation Club Pekanbaru, the data in this research were all populations which consists of 10 people. The instrument carried out in this research was a Balke 15 minute test, which aims to measure aerobic endurance. The data in this research was processed by using statistics, to test the normality by the lilliefors test at a significant level of 0.05. The hypothesis proposed, that there was an effect of Triangle Run exercise in aerobic endurance. Based on the t-test analysis, Tvalue was 13,65 and Ttable was 1,833 which means Tvalue > Ttable. Based on statistical data analysis, Based on statistical data analysis, the mean of Pre-Test was 39,08, and the mean of post-test was 47,688, which means the data were normal. Therefore, it can be concluded that there was an effect of the Triangle Run exercise in aerobic endurance on the volleyball team man of Generation Club Pekanbaru.Key Words: Triangle Run, Aerobic Endurance